Integrated mRNA–miRNA transcriptome profiling of blood immune responses potentially related to pulmonary fibrosis in forest musk deer - Qi, Wen-Hua; Hu, Li-Fan; Gu, Yu-Jiawei; Zhang, Xiao-Yan; Jiang, Xue-Mei; Li, Wu-Jiao; Qi, Jun-Sheng; Xiao, Guo-Sheng; Jie, Hang (Frontiers in Immunology, 2024)
Forest musk deer (FMD, Moschus Berezovskii) is a critically endangered species world-widely, the death of which can be caused by pulmonary disease in the farm.Pulmonary fibrosis (PF) was a huge threat to the health and survival of captive FMD.MicroRNAs (miRNAs) and messenger RNAs (mRNAs) have been involved in the regulation of immune genes and disease development. However, the regulatory profiles of mRNAs and miRNAs involved in immune regulation of FMD are unclear.In this study, mRNA-seq and miRNA-seq in blood were performed to constructed coexpression regulatory networks between PF and healthy groups of FMD. A total of 2744 differentially expressed genes (DEGs) and 356 differentially expressed miRNAs (DEmiRNAs) were identified in the PF blood group compared to the healthy blood group. Among them, 42 DEmiRNAs were negatively correlated with 20 immune DEGs from a total of 57 correlations. The DEGs were significantly associated with pathways related to CD molecules, immune disease, immune system, cytokine receptors, T cell receptor signaling pathway, Th1 and Th2 cell differentiation, cytokine-cytokine receptor interaction, intestinal immune network for IgA production, and NOD-like receptor signaling pathway. There were 240 immune-related DEGs, in which 186 immune-related DEGs were up-regulated and 54 immune-related DEGs were down-regulated. In the protein-protein interaction (PPI) analysis of immune-